The relationship between patient satisfaction and effectiveness of insulin-based therapy for type 2 diabetes mellitus at Ulin Regional Public Hospital, Banjarmasin - Risya Mulyani; Dedi Hartanto (Pharmaciana, 2018)
Diabetes Mellitus (DM) can cause significant problems to the quality of life as it may increase the risk of complications. Dissatisfaction with therapy also contributes to its low effectiveness. Therapeutic satisfaction has an essential role in DM management, i.e., to optimize the effectiveness of the treatment. It is also believed to affect the decision-making process regarding patients‘ healthrelated issues. A routine assessment of the satisfaction of DM patients is useful for health professionals in identifying the potential problems experienced by those who are in the middle of DM treatment. This study aimed to determine the relationship between patient satisfaction and effectiveness of insulin-based therapy for type 2 DM at Ulin Regional Public Hospital, Banjarmasin. This research is a nonexperimental study with a cross-sectional design. The data were collected prospectively with purposive sampling method from the type 2 DM patients at the Pharmacy Installation of Ulin Regional Public Hospital, Banjarmasin. While the therapeutic satisfaction data were obtained using the Patient Satisfaction with Insulin Therapy (PSIT) questionnaire, the effectiveness of the therapy was identified by examining the HbA1c values. Fifty-six (56) respondents participated and filled in the questionnaire, and the answers were processed with bivariate analysis, namely the chi-square test. The results showed that the respondents‘ satisfaction with the treatments was mostly on a medium level according to 33 patients (58.9%). However, only 3.6% respondents found the therapy effective (HbA1c <6.5%). The remaining 96.4% thought that it was less effective in controlling diabetes. Based on the statistical analysis results, there is a significantly positive relationship between patient satisfaction and HbA1c value ([r= 0.828]; [p= 0.000]). There is also a significant positive relationship between patient satisfaction and the effectiveness of therapy in patients with type 2 diabetes at the Pharmacy Installation of Ulin Regional Public Hospital, Banjarmasin.